2018
DOI: 10.3126/jpn.v8i2.20863
|View full text |Cite
|
Sign up to set email alerts
|

A histopathological study of granulomatous lesions

Abstract: Background: Granulomas are the commonest lesions that the pathologists come across in routine practice. Granulomatous inflammation is a special type of chronic inflammation that is a manifestation of many infective, toxic, allergic, autoimmune and neoplastic diseases and also conditions of unknown etiology. The aim of this study is to analyze different granulomatous lesions and to find the frequency and etiology of all granulomatous lesions.Materials and Methods: The study included a total of 218 granulomatous… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 5 publications
0
2
0
Order By: Relevance
“…Sehgal et al observed in their study that granulomas can be seen in draining lymph nodes of patients with malignancy and in both Hodgkin's disease and non-Hodgkin's lymphoma. 23 Sometimes, cytological findings of granulomas in carcinoma and lymphoma obscure primary malignancy and may favour the underdiagnosis of such cases as infectious etiologies. For appropriate and timely management of these cases, proper identification of the cause of granulomatous inflammation is mandatory.…”
Section: Discussionmentioning
confidence: 99%
“…Sehgal et al observed in their study that granulomas can be seen in draining lymph nodes of patients with malignancy and in both Hodgkin's disease and non-Hodgkin's lymphoma. 23 Sometimes, cytological findings of granulomas in carcinoma and lymphoma obscure primary malignancy and may favour the underdiagnosis of such cases as infectious etiologies. For appropriate and timely management of these cases, proper identification of the cause of granulomatous inflammation is mandatory.…”
Section: Discussionmentioning
confidence: 99%
“…They may also [3] coalesce to form multinucleated giant cells. The aetiology of granulomatous disorders are broadly classified into infections, autoimmune, toxic, allergies, [4,5] neoplastic, foreign body, fungal, helminthic, bacterial, and unknown causes. The pathogenesis of granulomas is hinged on the production of mediators from \2 For Reprint Contact: jrbcs.org@gmail.com J Res Bas Clin Sci | Vol 2 | No 2 | 2021 activated macrophages, especially interferon-gamma (INF-γ) from myeloid precursors maturing into [6] monocytes in the peripheral circulation.…”
Section: Introductionmentioning
confidence: 99%